Satellite selection in the context of an operational GBAS. Issue 1 (27th February 2019) - Gerbeth, Daniel; Caamano, Maria; Circiu, Mihaela‐Simona; Felux, Michael
Abstract: When incorporating multiple constellations into future ground based augmentation systems (GBAS), a problem with limited VDB (VHF data broadcast) capacity might arise. Furthermore, the number of airborne receiver tracking channels could be insufficient to use all visible satellites. One way to cope with these issues is to perform a satellite selection to limit the number of used satellites with minor impact on performance. This paper investigates different factors that constrain the approach of simply selecting "the best set in every epoch" and shows how to overcome some limitations. These constraints include limitations in satellite visibility, loss of satellites during approach (i.e. in curves), and convergence times in the airborne processing until satellites are usable. Various protection level simulations are performed to show the influence of the named factors on the nominal performance. Taking into account all these contextual influences, results show satellite selection is still applicable in GBAS ground stations.